Quantum Markov Chains and Ising model on Cayley tree - Mukhamedov, Farrukh; Saburov, Mansoor (WorldScientific, 2013)
In the present paper wes tudy forward Quantum Markov Chains (QMC)associated with Ising model on Cayley tree of order k. Using the tree structure of graphs, we give a construction of Quantum Markov Chains on a Cayley tree. By means of such construction we prove the existance of a phase transition for the Ising model on a Cayley tree of order k in QMC scheme. By the phase transition we mean the existance of two not quasi equivelant QMC for the given family of interaction operators.